2002
DOI: 10.1348/000709902320634564
|View full text |Cite
|
Sign up to set email alerts
|

The writing approaches of secondary students

Abstract: The factor structure of secondary writing reflected three process dimensions. The first factor, Elaborative-Expressive, describes a writing strategy based on personal investment and audience concern. The second factor, Planful-Procedural, denotes sticking to a plan, following the rules, and 'preparing' for writing. Achieving-Competitive, the third factor, reflects a 'teacher pleasing' strategy or doing only what needs to be done to get a good grade. Two factors from the college model, Elaborative and Procedura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
6
38
0
2
Order By: Relevance
“…Thus, a self-reporting writing questionnaire can be useful for discriminating between groups. Other researchers applying self-reporting writing questionnaires showed that it is possible to detect individual differences between writers with self-reporting writing questionnaires (Galbraith, 1996(Galbraith, , 1999Janssen & Overmaat, 1990;Lavelle, Smith, & O'Ryan, 2002;Torrance et al, 1994Torrance et al, , 1999Torrance et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a self-reporting writing questionnaire can be useful for discriminating between groups. Other researchers applying self-reporting writing questionnaires showed that it is possible to detect individual differences between writers with self-reporting writing questionnaires (Galbraith, 1996(Galbraith, , 1999Janssen & Overmaat, 1990;Lavelle, Smith, & O'Ryan, 2002;Torrance et al, 1994Torrance et al, , 1999Torrance et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires about different aspects and/or configurations of writing processes (Kieft et al 2006(Kieft et al , 2008Lavelle et al 2002;Torrance et al 1994Torrance et al , 1999Torrance et al , 2000 are an example of such offline measures. The use of offline measurements have been criticised as inaccurate reflections of the underlying process.…”
mentioning
confidence: 99%
“…These researchers, as well as others who found that children's writing self-efficacy is related to their writing performance (see Bandura, 1984;Lavelle et al, 2002;Meier et al, 1984;Pajaras & Johnson, 1996;Wray, 1993), note that children can draw on a variety of resources when developing their self-efficacy in a certain domain, previous achievement being one of them. Our results indicate that one of these resources could also be their writing knowledge.…”
Section: Discussionmentioning
confidence: 96%